2022
DOI: 10.1001/jamanetworkopen.2022.36676
|View full text |Cite
|
Sign up to set email alerts
|

Interventions Associated With Reduced Loneliness and Social Isolation in Older Adults

Abstract: ImportanceLoneliness and social isolation are public health concerns faced by older adults due to physical, cognitive, and psychosocial changes that develop with aging. Loneliness and social isolation are associated with increased morbidity and mortality.ObjectiveTo evaluate interventions, targeting older adults, associated with a reduction in loneliness and social isolation.Data SourcesOVID, CINAHL, CENTRAL, Embase, PsychINFO, Web of Science, and Scopus were searched from inception to March 2020.Study Selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(71 citation statements)
references
References 141 publications
0
35
0
Order By: Relevance
“…Recent meta-analyses modeling CBT interventions for loneliness found average effect sizes of 0.47 and 0.52. 6,24 Although this study employed a quasi-experimental design, the use of a propensity-matched comparison group to adjust for regression to the mean helped to strengthen the final conclusions. Ideal experimental designs are often not achievable in process improvement environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent meta-analyses modeling CBT interventions for loneliness found average effect sizes of 0.47 and 0.52. 6,24 Although this study employed a quasi-experimental design, the use of a propensity-matched comparison group to adjust for regression to the mean helped to strengthen the final conclusions. Ideal experimental designs are often not achievable in process improvement environments.…”
Section: Discussionmentioning
confidence: 99%
“…The current intervention's adjusted effect size of 0.49 compares favorably with a variety of other psychological interventions and other direct attempts to mitigate loneliness. Recent meta‐analyses modeling CBT interventions for loneliness found average effect sizes of 0.47 and 0.52 6,24 …”
Section: Discussionmentioning
confidence: 99%
“…Our finding that lonely individuals report more unmet healthcare needs, irrespective of sociodemographic and health factors, could also indicate that loneliness contributes to a persistent feeling of dissatisfaction, reinforcing the feeling that a need is not being met. Interventions aimed at reducing loneliness have been described in numerous reviews, ranging from personal contact interventions (eg, friendly visitor programmes) to animal/pet therapy and various technological interventions51 52; however, these reviews found small to medium effect sizes and note significant limitations of the included studies such as variable study quality, small sample sizes, distinct populations (eg, community vs nursing homes) and incomparable loneliness measures. Efforts to address loneliness will remain stalled until findings from robust interventions are available.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of interventions found to increase oxytocin signaling include skin-to-skin stimulation like massages, gustatory stimulation, positive human interactions like cohabitation and safe, consensual sexual interactions, and interaction with pets ( 48 ). Notably, a systematic review and meta-analysis of 44 studies found that animal therapy is more effective than psychotherapy and occupational therapy, among other types of interventions, in reducing loneliness among older adults ( 94 ).…”
Section: Interventions For Treating and Preventing Lonelinessmentioning
confidence: 99%